Exploring the Nutritional Composition and Bioactive Compounds in Different Cocoa Powders - María del Carmen Razola-Díaz; María José Aznar-Ramos; Vito Verardo; Sonia Melgar-Locatelli; Estela Castilla-Ortega; Celia Rodríguez-Pérez (MDPI AG, 2023)
Cocoa, the main derivative of the seeds of Theobroma cacao L., has been recognized to have several effects on human health including antioxidant and neuro- and cardio-protective effects, among others. These effects have been attributed mainly to its bioactive compounds. In this context, the aim of this work is to evaluate the nutritional composition, bioactive compounds (i.e., phenolic compounds, procyanidins and methylxanthines) and the antioxidant activity of seven different cocoas (alkalized and non-alkalized) from different origins (Peru, Venezuela, Ivory Coast, Dominican Republic, and West Africa). It represents the first stage of a larger project aiming to find high polyphenol cocoa-based nutritional strategies and related biomarkers that may potentiate brain plasticity and cognitive function. Cocoa powders were extracted by ultrasound-assisted technology, and the total phenolic content (TPC) was measured by Folin-Ciocalteu. Methylxanthines (caffeine and theobromine) and procyanidin contents were determined by HPLC-FLD-DAD, and the antioxidant activity was assessed through DPPH, ABTS and FRAP assays. Non-alkalized cocoas showed higher phenolic and procyanidin contents and higher antioxidant activity compared to the alkalized ones. A strongly significant (p < 0.05) positive correlation between the antioxidant activity and the TPC, especially with the total procyanidin content, but not with methylxanthines was found. In conclusion, the non-alkalized cocoas, especially the one from Peru, were the best candidates in terms of bioactive compounds. The cocoa from Peru had a TPC of 57.4 ± 14.4 mg of gallic acid equivalent/g d.w., 28,575.06 ± 62.37 µg of catechin equivalents/g d.w., and 39.15 ± 2.12 mg/g of methylxanthines. Further studies should be undertaken to evaluate its effect on brain plasticity and cognitive function.